THE STRUCTURE OF THE COMMUNITY AND THE DIVERSITY OF PLANKTON TYPES FOUND IN THE CURUG GUMAWANG AREA, PADARINCANG DISTRICT, SERANG-BANTEN DISTRICT - Hermawan, Hermawan (Transpublika Publisher, 2024)
The research was conducted to determine the community structure and diversity of plankton types in Gumawang Waterfall, Padarincang Village, Padarincang District, Serang-Banten Regency. This research was carried out in February 2024 for 1 month. This research was carried out on 4 plankton samples, with results obtained from 12 types of plankton species. The plankton that dominates or is often found at these 4 points is the Achnanthes sp type with a number of around 170 species. The results of calculations using the Species Diversity Index obtained a result of 2.176744285, this shows that the diversity of plankton species found in Gumawang Waterfall, Padarincang Village, Padarincang District, Serang-Banten Regency is in the